[tex]\displaystyle a=\left(\begin{array}{ccc}a&4\\3&-a\\\end{array}\right);~a(1)= \left(\begin{array}{ccc}1&4\\3&-1\\\end{array}\right) ;~a(-1)= \left(\begin{array}{ccc}-1&4\\3&1\\\end{array}\right)\\ \\a(1)+a(-1)= \left(\begin{array}{ccc}1&4\\3&-1\\\end{array}\right)+\left(\begin{array}{ccc}-1&4\\3&1\\\end{array}\right)=\\ \\=\left(\begin{array}{ccc}1+(-1)&4+4\\3+3&-1+1\\\end{array}\right)= \left(\begin{array}{ccc}0&8\\6&0\\\end{array}\right)\\ \\ a(1)+a(-1)=\left(\begin{array}{ccc}0&8\\6&0\\\end{array}\right)[/tex]